2014
DOI: 10.1007/s11295-014-0805-2
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Quercus glauca (Fagaceae), a dominant tree of East Asian subtropical evergreen forests, based on three chloroplast DNA interspace sequences

Abstract: Historical geoclimatic events have shaped the distribution patterns and intraspecific divergence of plants. Numerous phylogeographical studies in China have focused on the Qinghai-Tibetan Plateau and surrounding areas due to the complex topography and high species diversity, but the impact of Neogene events and Quaternary climatic change on the flora of subtropical China remains poorly understood. Quercus glauca, a widespread tree of East Asian subtropical evergreen forests, has rich fossil records dating back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 86 publications
5
75
2
Order By: Relevance
“…; Xu et al . ). This global cooling and associated environmental changes probably seriously affected the distribution of C. carlesii and allowed the differentiation of two lineages into distinct eastern and western lineages (similarly to the distribution contraction observed during the LGM).…”
Section: Discussionmentioning
confidence: 97%
“…; Xu et al . ). This global cooling and associated environmental changes probably seriously affected the distribution of C. carlesii and allowed the differentiation of two lineages into distinct eastern and western lineages (similarly to the distribution contraction observed during the LGM).…”
Section: Discussionmentioning
confidence: 97%
“…Heterobalanus was a response to the HHM uplift. A phylogeographic study of the warm evergreen oaks, Quercus glauca, revealed that two major haplotype lineages (southwest China versus southeast China and East China Sea) were separated by the topographic barrier of the Himalayan uplift in the Miocene which allowed the two lineages to diverge (Xu et al 2015), providing evidence that the colonization event was caused by the Himalayan uplift.…”
Section: The Hhm Uplift Climatic Cooling and Colonizationmentioning
confidence: 99%
“…Thus, various studies have focused on species that are ecologically minor components of EBLF or failed to cover geographical key areas such as those adjacent to the current southern EBLF boundary (Li, Yan, & Ge, 2012;Tian et al, 2018;Wang et al, 2015); their results may therefore not be representative for the biome as a whole. On the other hand, most studies of major or widely distributed EBLF species have to date only used cytoplasmatic markers (Sun, Hu, Huang, & Vargas-Mendoza, 2014;Tian et al, 2015;Xu et al, 2015;Fan et al, 2016; but see Shi et al, 2014); their results do hence not provide any insights into important processes such as pollen-mediated gene flow and secondary admixture. As a result, we still ignore many aspects of past population and range dynamics in subtropical China that could provide valuable insights into the past evolution of the EBLF biome.…”
Section: Introductionmentioning
confidence: 99%